Automotive control: from concept to experiment to product - Hanselmann, H. (1996 IEEE International Symposium on Computer-Aided Control System Design, 1996)
Without appropriate tools to implement new controllers quickly and safely, the tightening development schedules cannot be met anymore. This paper addresses the issue of rapid control prototyping (RCP). With RCP there is a smooth and fast transition from a design concept to its experimental verification.